Safety during maintenance of highways delegate information : Friday 12 July 1996, One Great George Street Conference Centre, the Institution of Civil Engineers, London. (Thomas Telford, 1996)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in July 1996.